1975
DOI: 10.2323/jgam.21.65
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Cell Wall Peptidoglycan From Clostridium Saccharoperbutylacetonicum Studied With Phage Endolysins and Gas Chromatography

Abstract: The enzymic digest of cell wall peptidoglycan from Clostridium saccharoperbutylacetonicum by phage HM 7 endolysin (N-acetylmuramyl-Lalanine amidase) was separated into two constituents on ion-exchange chromatography. One was a polysaccharide, which contained N-acetylglucosamine and N-acetylmuramic acid in the molar ratio of 1.00: 0.78. This polysaccharide was digested by phage HM 3 endolysin (N-acetylmuramidase), and the digested product was a saccharide composed of N-acetylglucosamine and N-acetylmuramic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The peptidoglycan has been described as composed of a matrix consisting of N-acetylglucosamine and N-acetylmuramic acid linked by ß-1,4 linkages and pentapeptide side chains comprising D-and L-alanine, D-glutamic acid, and either L-lysine or mesodiaminopimelic acid (Ogata et al, 1975;Rose, 1976). Recent developments in analytical biochemistry have made it possible to estimate the bacterial biomass in different environments by measuring the specific biochemical constituents of bacteria, such as Downloaded by [University of California, San Diego] at 12:36 29 June 2016 adenosine triphosphate (Karl, 1979), total lipid fatty acids (White et al, 1979), and muramic acid (Millar and Casida, 1970;Moriarty, 1977;Findlay et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptidoglycan has been described as composed of a matrix consisting of N-acetylglucosamine and N-acetylmuramic acid linked by ß-1,4 linkages and pentapeptide side chains comprising D-and L-alanine, D-glutamic acid, and either L-lysine or mesodiaminopimelic acid (Ogata et al, 1975;Rose, 1976). Recent developments in analytical biochemistry have made it possible to estimate the bacterial biomass in different environments by measuring the specific biochemical constituents of bacteria, such as Downloaded by [University of California, San Diego] at 12:36 29 June 2016 adenosine triphosphate (Karl, 1979), total lipid fatty acids (White et al, 1979), and muramic acid (Millar and Casida, 1970;Moriarty, 1977;Findlay et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…These include paper chromatography (Yamada and Komagata, 1970), thin layer chromatography (Boone and Pine, 1968), ion exchange chromatography (Vasstrand et al, 1980), enzymatic analysis (Ogata et al, 1975), and gas chromatography. Several derivatization techniques have been applied to the gas Chromatographie procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Paper chromatography and TLC have been used primarily to provide a rapid qualitative assessment of the wall amino acid composition and to detect diagnostic diamino acids [4,5]. An established technique, applied only rarely to bacterial amino acids [6,7], is the conversion of amino acids into volatile derivatives and their analysis by gas chromatography (GC) [8]. This approach is of potential value since it provides reliable quantitative data on wall amino acids without the use of an amino acid analyser.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…The chemical constituents of the cell walls of various species of the genus Clostridium were qualitatively determined by Cummins and colleague [2,3] and these results were used for classification of this genus [19]. Although there are a few studies on the quantitative chemical analyses of peptidoglycans of some clostridia [12,13,15], there are no reports on various types of Clostridium botulinum, except type A [21]. Our previous studies [24] on the cell walls of C. botulinum type A have shown that the peptidoglycan is of the directly cross-linked diaminopimelic acid (DAP)-containing type in which the cross-linkage of peptide moiety extends from the r-amino group of DAP of one peptide to the carboxyl group of D-alanine of another adjacent peptide subunit.…”
mentioning
confidence: 99%